Preventive effects of combinative natural foods produced by elite crop varieties rich in anticancer effects on N‐nitrosodiethylamine‐induced hepatocellular carcinoma in rats. Issue 1 (29th November 2018) - Zheng, Jingui; He, Jun; Liao, Sufeng; Cheng, Zuxin; Lin, Jinke; Huang, Ke; Li, Xiaocen; Zheng, Kaibin; Chen, Xuanyang; Lin, Lihui; Xia, Fagang; Liu, Jianghong; et al.
Abstract: The World Cancer Research Fund International has released 32 anticancer effects (ACEs) that targeted every stage of cancer processes. Thus, we designed two formulas of natural food combination Diet I and Diet II, mainly produced by elite crop varieties rich in ACEs with different mixture ratios, and evaluated their cancer preventive effects on N‐ nitrosodiethylamine (NDEA)‐induced hepatocarcinogenesis. After 20 weeks of dietary intervention, Diet I and Diet II reduced incidence, size, and number of hepatic nodules ( p < 0.01) and prevented hepatic tumor formation in NDEA‐induced hepatocarcinogenesis rats. Low‐grade hepatic dysplasia incidence was 20% for Diet II and 40% for Diet I, and apparent hepatocellular carcinomas (HCC) rates were both 0, while 90% HCC in control diet treatment group ( p < 0.01). Diet I and Diet II ameliorated abnormal liver function enzymes, reduced serum alpha fetal protein, tumor‐specific growth factor, dickkopf‐related protein 1, tumor necrosis factor‐alpha and interleukin‐6 levels, regulated hepatic phase I and II xenobiotic‐metabolizing enzymes, enhanced antioxidant capacity, suppressed NDEA‐initiated oxidative DNA damage, and induced apoptosis coupled to down‐regulation of proinflammatory, invasion, and angiogenesis markers. Daily intake of combination diet produced from ACEs‐rich elite crop varieties can effectively prevent or delay occurrence and development of NDEA‐induced hepatocarcinogenesis in rats. Abstract : In this paper, the pure natural food combinations Diet I and Diet II, which were mainly produced by elite crop varieties rich in anticancer effects (ACEs) with different mixture ratios, prevented N‐nitrosodiethylamine‐induced hepatocarcinogenesis in rats effectively, the low‐grade hepatic dysplasia incidence was 20% for Diet II and 40% for Diet I, and the apparent hepatocellular carcinoma (HCC) rates of both were 0, while the apparent HCC rate of the control diet treatment rats was 90% (P<0.01). This study indicated excellent prospects of daily dietary for cancer prevention and the importance of discovery and creation of ACEs‐rich crop varieties.